Pengaruh Kompensasi Financial dan Non Financial terhadap Kinerja Pegawai Bank Perkreditan Rakyat Modern Express Cabang Serui Kabupaten Kepulauan Yapen - Agoeng Karyanto; Korenus Reri; Waspada Meliala (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to determine the significant influence of financial and non-finansial compensation on employee performance at the Modern Express People's Credit Bank, Serui Branch, Yapen Islands Regency. Modern Express People's Credit Bank, Serui Branch, Yapen Islands Regency is a finansial institution that operates in the banking sector. As an organization. For this reason, it is necessary to carry out more in-depth and specific research regarding the influence of financial and non-financial compensation on employee performance at the Modern Express People's Credit Bank, Serui Branch, Yapen Islands Regency. This research uses a quantitative analysis method where surveys and questionnaires are carried out as tools to collect data. The data analysis techniques used consist of validity and reliability tests, normality tests, multiple linear regression, F tests and t tests. The sample used in this research was 33 respondents. The results of this research show that there is a significant influence. Based on the results of statistical tests using the SPSS 25 application, the results of financial compensation on employee performance obtained a significant value of 0.000 < 0.05, the results of non-financial compensation on employee performance obtained a significant value of 0.000 < 0.005, the results were jointly significant. The same thing carried out using the T test is 0.000 < 0.005, which means that there is a significant influence of financial and non-finansial compensation on employee performance.